PENGARUH KOORDINASI SIMPANG BERSINYAL TERHADAP WAKTU TEMPUH PENGGUNA JALAN (STUDI KASUS SIMPANG PEGADAIAN DAN SIMPANG ALUN-ALUN LAMA UNGARAN) - Bimantara, Firmandhi Sahid; rachmat, rachmat; soedarsono, soedarsono (Pondasi, 2023)
The increasing volume of vehicles creates a traffic problem that often occurs in urban areas, long time of travel time delays experienced by road users, therefore the government's role is needed to overcome these problems. The problems that occur make road users experience twice the red time which makes the travel time longer. This research was focused on evaluating the existing cycle time settings at the Alun-alun lama and Pegadaian intersections in Semarang Regency with the aim of obtaining optimal cycle times. The main objectives of this study include evaluating the existing cycle timing, analyzing intersection control using the greenwave method, evaluating the effectiveness of intersection coordination, and determining the benefits of intersection coordination. The recommendations put forward include implementing various and coordinated cycle timings at the intersection of Pegadaian and Alun-alun Lama by utilizing the greenwave method. Based on literature analysis, research, and field observations it is known that the coordination of signalized intersections can reduce travel time for road users. The research findings show that setting the current cycle time requires longer time than the proposed new cycle time. The results of controlling the intersection using the greenwave method managed to reduce travel time by up to 27.9% of the total time required. This shows the importance of varying timing to achieve optimal performance.